First Nations Politics in a Climate of Refusal: Speaking and listening but failing to hear. (3rd April 2018) - Grehan, Helena
Abstract : As a nation, Australians celebrate their cultural heritage through purchasing works of art by leading Aboriginal and Torres Strait Islander artists. These works are held in all major State-owned galleries and in most of the private collections of serious art buyers in the country. Australians also champion and support key artistic works in dance and performance. There remains, however, a distinct tension between the willingness of (successive) governments to celebrate the symbolic value of Aboriginal and Torres Strait Islander peoples' creative works and governmental readiness to participate in or endorse any performance that might usher in meaningful structural or material change for First Nations people who, in 2018, are still excluded from the Australian Constitution. The focus of this paper is to consider the performative qualities of both the 'Uluru Statement from the Heart' (2017), written by Aboriginal and Torres Strait Islander leaders and presented to the people of the nation and to the government as an invitation to work together to achieve 'Constitutional reforms' for the First Nations people of Australia, and the Government's response to this invitation via their Media Release and subsequent interviews. An analysis of the modes of address, the language used, and the aesthetic and ethical questions raised by each text, provides insight on the politics of speaking and listening in the current Australian political climate.